Impact of Oil Price Changes on Selected Economic Sectors in the Czech Republic - Pavelková, Dominika (2019)
This thesis examines if there is a significant impact of oil price changes on the Czech economy and its sectors. In the theoretical part of the thesis, I present the theoretical background and existing research, and in the practical part, I employ a regression analysis. Using the error correction and ARIMA models, I developed a model for each sector based on the data from 1995Q1 to 2018Q2. In contrast to the expectations, the results suggest that the oil price have no significant impact neither on the Czech economy as a whole nor on the manufacturing industry. The significant impact of oil price was found at two oil-consuming sectors and one oil-non-consuming sector. These findings suggest that the oil price does not have a significant impact on the Czech economy and that it is more likely driven by foreign demand.